2023
DOI: 10.3390/vaccines11040839
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Refusal and Delay among Adults in Italy: Evidence from the OBVIOUS Project, a National Survey in Italy

Abstract: Background: Vaccine hesitancy was defined by the World Health Organization (WHO) in 2019 as a major threat to global health. In Italy, reluctance to receive vaccines is a widespread phenomenon that was amplified during the COVID-19 pandemic by fear and mistrust in government. This study aims to depict different profiles and characteristics of people reluctant to vaccinate, focusing on the drivers of those who are in favor of and those who are opposed to receiving the COVID-19 vaccine. Methods: A sample of 10,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…For example, a UK study found that women were more likely to be vaccinehesitant [24]. Higher rates of vaccination refusal among females have also been reported in other countries, including Italy and Japan [12,15]. A consistent finding across different settings and times was that distrust is still a leading contributor to vaccine hesitancy and that this issue needs to be addressed to increase vaccine uptake.…”
Section: Discussionmentioning
confidence: 92%
“…For example, a UK study found that women were more likely to be vaccinehesitant [24]. Higher rates of vaccination refusal among females have also been reported in other countries, including Italy and Japan [12,15]. A consistent finding across different settings and times was that distrust is still a leading contributor to vaccine hesitancy and that this issue needs to be addressed to increase vaccine uptake.…”
Section: Discussionmentioning
confidence: 92%
“…Despite the apparent safety and efficacy of the vaccine (Bar-On et al, 2021;Dagan et al, 2021), a high percentage of people from all over the world did not get vaccinated until the present day, for various reasons (Frankenthal et al, 2022;Gori et al, 2023;Rego et al, 2023;Song & Lee, 2023;Takoudjou Dzomo et al, 2023;WHO, 2023). Many developed countries reported relatively low vaccination rates in their populations (WHO, 2023) despite offering free vaccines to all eligible subjects (there were almost no sub-groups of the adult population that were not allowed to get vaccinated for health reasons) (Barda et al, 2021;Hodgson et al, 2021;Polack et al, 2020;Zhu et al, 2020), and in spite of repetitive outbreaks of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the reported low vaccination rates were perceived as a major threat to the general effort to combat the pandemic and a risk to public health (WHO, 2019). Vaccine refusal rates among the eligible adult population were relatively high all over the world (WHO, 2023) but varied greatly among different countries and regions (Frankenthal et al, 2022;Gori et al, 2023;Khubchandani et al, 2022;Rego et al, 2023;Song & Lee, 2023;Takoudjou Dzomo et al, 2023). For example, an Israeli study, which included nearly 3000 households (1827 Jews and 1171 Arabs) revealed that 16.3% of the sample population hesitated/refused to get vaccinated despite the availability of the vaccine to them (Frankenthal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations